2022
DOI: 10.9745/ghsp-d-21-00761
|View full text |Cite
|
Sign up to set email alerts
|

Examining Roles, Support, and Experiences of Community Health Workers During the COVID-19 Pandemic in Bangladesh: A Mixed Methods Study

Abstract: During the first wave of the coronavirus disease (COVID-19) pandemic in Bangladesh, across all health areas, community health workers (CHWs) described a slight decrease in the routine services they were able to provide due to restrictions in movement posed by lockdowns and other challenges.nThe government and various nongovernmental organizations provided supportive mechanisms to CHWs through training, supplies, and supportive supervision; however, these supports were not always uniformly distributed across ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“… 23 , 24 , 25 , 26 , 32 , 33 , 35 , 45 Besides, several previous studies reported challenges regarding the number and performance of health staff. 56 , 57 , 58 , 59 Several studies have indicated an insufficient supply of personal protective equipment (PPE) and its poor quality triggers the possibility of infection. This review captured no evidence of M&E focusing on essential medical services during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 , 25 , 26 , 32 , 33 , 35 , 45 Besides, several previous studies reported challenges regarding the number and performance of health staff. 56 , 57 , 58 , 59 Several studies have indicated an insufficient supply of personal protective equipment (PPE) and its poor quality triggers the possibility of infection. This review captured no evidence of M&E focusing on essential medical services during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Among the few outreach initiatives launched in France in 2020 ( 26 ), CORHESAN influenced government discussions and contributed to the establishment of the MédiLAC national strategy from February 2021. More generally, WHO and UNICEF published guidance on the use of community health care workers in the context of the COVID-19 pandemic in 2020 ( 38 ), and several other outreach experiences have been described abroad, to promote appropriate symptom management, preventive behaviours, testing or vaccination in French Guiana ( 39 , 40 ), in the USA – particularly among the Latinx community ( 41–51 ), in Mexico ( 52 ), in the UK ( 53 ), in Kenya, Senegal and Uganda ( 54 ), in Bangladesh ( 55 ) or in Indonesia ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Well facilitated, equipped and trained CHWs contribute to resilience of community health systems [2]. As community members themselves, CHWs provide a unique opportunity to facilitate an effective linkage to care [3]. The roles of CHWs in many contexts extend beyond health promotion to community management of mild cases for example as part of integrated community case management of childhood illnesses (iCCM) of pneumonia, diarrhoea, and malaria, providing oral and injectable contraceptives, treating malnutrition, and administering vaccines among children [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%